Desertos e pântanos alimentares em uma metrópole brasileira - Olivia Souza Honório (2020)
Introduction: The terms "food desert" and "food swamps"are terminology for classification the food environment, being considerate physical access and socioeconomic condition. Food deserts are characterized as socially vulnerable neighborhoods that lack or have limited physical access to healthy food. Food swamps are neighborhoods where physical access is facilitated for unhealthy foods. Objective: To describe the comunity food envirinmment and identify food deserts and food swamps in a Brazilian metropolis. Metodology: Ecologic study, conducet in Belo Horizonte city. The units of analysis used are census tract and circular buffers of 400, 800 and 4000 metres. The social environment variables aused are: income, number of household, population, literacy, race, availability of essential services (water and electric power supply and garbage collection) and Health Vulnerability Index (HVI). The comunity food environment variables come from two sources of government data. The establishments that sell food are classify into: establishments that sell predominantly in natura food, establishments tht sell predominantly ultra-processed food and mixed establishments. Were selected four metodologys for to evaluate the food deserts and food swamps, consideraded the frequency in the literature and possiblity with possibility to repeat. Used QGIS 2.14.9 and SPSS 15.0 for data analyze. Results: The mixed establishment and establishment sell predominantly ultra-processed food are the most frequently in Belo Horizonte city, represented 42,90% and 46,92% respectively, and snack bar (25,36%) and restaurants (24,52%) are the types most frequently. Approximately 25% of the census tracts don't have estabilishment sell foods and 77,52% don't have estabilishment sell predominatly in natura food. When to evaluate tha food availability stratified for per capita income of census tracts, checked low income censu tracts have little availability all types estabilishments. In the identification of food deserts, the methodology proposed by CAISAN (37.70%) and CDC (39.10%) identified more census sectors that fit this classification. Only the methodology proposed by CAISAN identified that food deserts were more frequent in lower income sectors. In relation to food swamps, the adapted CAISAN methodology (58.50%) and that of the CDC (66.58%) identified a higher percentage of sectors that received this classification. When stratifying by income, the methodology proposed by Hager and collaborators identified that food swamps were more frequent in sectors with lower income, the other methodologies showed the opposite. The sectors classified as food deserts had worse socioeconomic conditions and worse access to essential services. Conclusion: The physical access of establishments sell food does not uniform distribution in the city, the low income areas have worse physical access of the all establishments types. The methodology for to identify food deserts and food swamps porposed to Brazilian reality have the better results. In addition, the present study found tha households localized in food desert have worse socioeconomic conditions and availability of the essential services.